Synthesis and Characterization of Cellulose Nata de Coco Inserted Nanoparticles Zn-Moringa Leaf Extract (Moringa oleifera) as Biodegradable plastic Banan Fruit Packaging - Ramadan; Ramadhan, La Ode Ahmad Nur; Zainal Syam Arifin (Journal of Pharmaceuticals and Natural Sciences, 2024)
Synthesis and characterization of cellulose nata de coco inserted nanoparticles of zinc-moringa leaf extract as biodegradable plastic for banana fruit packaging has been carried out. This study aims to determine the characteristics, biodegradability and preservation activity of biodegradable plastic cellulose nata de coco inserted zinc nanoparticles-moringa leaf extract. The research process was carried out through the nata de coco synthesis stage, zinc nanoparticle synthesis-moringa leaf extract and the manufacture of biodegradable plastics. The success of this synthesis is evidenced by being characterized using a UV-Vis spectrophotometer, FTIR spectrophotometer and digital optical microscope. The results of UV-Vis spectrophotometer analysis showed that the zinc nanoparticles formed had an estimated particle size of 85.72-92.92 nm and were stable. The results of FTIR analysis on Moringa leaf extract showed the presence of -OH, C-H, C=O, C=C and C-O groups. In the biodegradable plastic film nata de coco-NPZn-moringa leaf extract, there was a peak shift in several functional groups marked at the peaks of wavenumbers 555.50 and 432.05 cm-1 which are ZnZP groups. Characterization using a digital optical microscope showed that zinc nanoparticlesThe synthesis is spherical, non-uniform, and has been well distributed on the cellulose surface of nata de coco. Biodegradation test on nata de coco-NPZn-Moringa leaf extract biodegradable plastic film using activated sludge system, test results show biodegradable plastic can be degraded 100% for 15 days. Preservation activities show that packaged bananas are still able to survive up to 8 days of post-harvest storage period. These results show the effectiveness of biodegradable plastic preservation of nata de coco-NPZn-moringa leaf extract biodegradable plastic which is quite good.